2020
DOI: 10.1101/2020.08.14.251538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential methylation as a mediator of COVID-19 susceptibility

Abstract: The COVID-19 outbreak shows a huge variation in prevalence and mortality on geographical level but also within populations. The ACE2 gene, identified as the SARS-CoV2 receptor, has been shown to facilitate the viral invasion and people with higher ACE2 expression generally are more severely affected. As there is a lot of variability in ACE2 expression between individuals we hypothesized that differential DNA methylation profiles could be (one of) the confounding factors explaining this variability. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…ACE2 expression in the lung could be regulated by enzymes that modify histones, including HAT1, HDAC2, and KDM5B (40). In both freshly isolated airway epithelial cells and human lung tissues, different patterns of ACE2 gene methylation near the transcription start site of the ACE2 gene were identified in populations with different age and gender (41). MicroRNAs (miRNAs) could be involved in decreasing ACE2 expression at mRNA levels as well.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 expression in the lung could be regulated by enzymes that modify histones, including HAT1, HDAC2, and KDM5B (40). In both freshly isolated airway epithelial cells and human lung tissues, different patterns of ACE2 gene methylation near the transcription start site of the ACE2 gene were identified in populations with different age and gender (41). MicroRNAs (miRNAs) could be involved in decreasing ACE2 expression at mRNA levels as well.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are also shown to be regulated by epigenetics [Zill et al, 2012; Chu et al, 2014]. It was predicted that there is differential methylation in ACE2 gene and that may be the cause of variability of its expression and it could be used to check the susceptibility of an individual to SARS-CoV-2 infection [Steyaert et al, 2020]. However, promoter DNA methylation of both ACE2 and TMPRSS2 was not quantified in subjects infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Along these findings, ACE2 profiles were also shown to display a significant correlation with histone modification-related genes in the human lungs [90]. Additionally, the results of another study have previously demonstrated that ACE2 promoter was hypermethylated in hypertensive patients with a significant difference between males and females [91], where COVID-19 patients as well have displayed differential methylation pattern in ACE2 of blood samples [92] which further requires testing in the respiratory samples.…”
Section: Epigenetic Variation Of Ace2mentioning
confidence: 70%